De novo peroxisome biogenesis revisited - Marten Veenhuis; Ida J. van der Klei (Microbial Cell)
We describe an alternative peroxisome formation pathway in yeast pex3 and pex19 cells, which relies on the existence of small peroxisomal remnants that are present in these cells. This groundbreaking result challenges current models prescribing that peroxisomes derive de novo from the ER. Our data also has major implications for the sorting pathway of specific peroxisomal membrane proteins (PMPs). We propose a novel sorting pathway for the PMPs Pex13 and Pex14 that is independent of the known Pex3/Pex19 machinery.